2020
DOI: 10.1182/bloodadvances.2020002396
|View full text |Cite
|
Sign up to set email alerts
|

T follicular helper phenotype predicts response to histone deacetylase inhibitors in relapsed/refractory peripheral T-cell lymphoma

Abstract: Histone deacetylase inhibitors (HDACi) are active agents for peripheral T-cell lymphoma (PTCL). Anecdotally angioimmunoblastic T-cell lymphoma (AITL) appears to respond better than PTCL–not otherwise specified (NOS) to HDACi. The new World Health Organization classification shows that a subgroup of PTCL carries similarities in phenotype and gene expression profiling to AITL, comparable to T follicular helper (TFH) cells. The disease might behave similarly to AITL when treated with HDACi. We analyzed 127 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Paola et al already conducted a retrospective study to show the efficacy of histone deacetylase inhibitors (HDACi) in PTCL-NOS with TFH versus non-TFH phenotypes. The response rate to HDACi in PTCL-NOS with a TFH cell phenotype was about twice as high as that of the non-TFH phenotype (56.5% vs. 29.4%, p -value = 0.0035) [ 34 ]. Therefore, our data suggest that new target agents under development or research for AITL might also be promising treatment strategies in other TFH lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Paola et al already conducted a retrospective study to show the efficacy of histone deacetylase inhibitors (HDACi) in PTCL-NOS with TFH versus non-TFH phenotypes. The response rate to HDACi in PTCL-NOS with a TFH cell phenotype was about twice as high as that of the non-TFH phenotype (56.5% vs. 29.4%, p -value = 0.0035) [ 34 ]. Therefore, our data suggest that new target agents under development or research for AITL might also be promising treatment strategies in other TFH lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps unsurprising, the PTCL subtypes characterized by the T follicular phenotype and defined by hallmark mutations in epigenetic regulators, namely AITL and PTCL-TFH, have been shown to more responsive to HDAC inhibition. A retrospective cohort of 164 patients reported higher response rates in patients with TFH phenotype (ORR 56.5%) than those with and in non-TFH phenotype patients (ORR 56.5% vs. 29.4% p = 0.0035) [73].…”
Section: Histone Deacetylase Inhibitorsmentioning
confidence: 96%
“…70 Ghione et al reported that relapsed/refractory patients with PTCL who showed either AITL or nPTCL-Tfh phenotypes had higher response rate to histone deacetylase inhibitors (HDACi), including romidepsine and belinostat, than those without. 72 Gene mutations were examined in some samples included in this study. Intriguingly, patients responsive to HDACi more frequently exhibited AITL-specific mutational profiles (mutations in TET2, and/or DNMT3A, and/or RHOA) 33 than those without, although the relationship between clinical efficacy and mutational profiles must be confirmed in a larger cohort.…”
Section: A "Precision Medicine Approach" To Utilize Genomic Informatimentioning
confidence: 99%
“…Intriguingly, patients responsive to HDACi more frequently exhibited AITL-specific mutational profiles (mutations in TET2 , and/or DNMT3A , and/or RHOA ) 33 than those without, although the relationship between clinical efficacy and mutational profiles must be confirmed in a larger cohort. 72 …”
Section: Translation Of Molecular Analysis To the Bed-side Management Of Ptcl Nosmentioning
confidence: 99%